Exploring Freudian Defense Mechanism Theory in the Portrayal of Paul Atreides in the Movie 'Dune’ - Mufidah Kutfiyah Sari; Rani Roanliq Lamahayu; Firsta Marchania Rachman; Aulia Nurul` Izza; Ega Citta Salsabilla; Rina Saraswati; Rizal Octofianto Datau (Publikasi Inspirasi Indonesia, 2023)
This study explores the complex character of Paul Atreides in the movie “Dune” (2021), using psychoanalysis theory to uncover the hidden behaviors that determine Paul's psyche. While many analyses of